Effect of sequential application of herbicides on yield and nutrient uptake of greengram (Vigna radiata L. Wilczek), soil microbial parameters and imazethapyr residue status in soil - Jinger, Dinesh; Sharma, Rajvir; Dass, Anchal; Shukla, Livleen; Singh, Shashi Bala (Annals of Agricultural Research, 2016)
The present field experiment was conducted at New Delhi during rainy season (2013) to evaluatethe effect of sequential application of herbicides on yield, nutrient uptake of greengram, soilmicrobial parameter and status of imazethapyr residue in soil after crop harvest. Sequentialapplication of herbicides found to be more efficient in improving yield, nutrient uptake bygreengram and soil microbial parameters compared to their one-time application. Pendimethalin@ 1 kg/ha pre-emergence (PE) followed by (fb) 1 hand weeding (HW) at 30 days after sowing(DAS) resulted in highest seed yield (1.1 t/ha), stover yield (1.85 t/ha), protein content (24.12%).The same treatment also recorded maximum nutrient uptake by the crop, lowest nutrient uptakeby weeds and maximum value of microbial biomass carbon (MBC) and dehydrogenase activity(DHA). However, this treatment did not differ significantly from pendimethalin @ 0.75 kg/ha PEfb imazethapyr @ 75g/ha POE at 30 DAS indicating that sequential application of herbicidescould be an efficient alternative to manage weeds in greengram, particularly under labourconstrained conditions. Imazethapyr degrades in soil by the time of crop harvest since no residueswere found in soil after greengram harvest.